2023
DOI: 10.1177/13548166231153908
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative forecasting of tourism demand for multiple tourist attractions with spatial dependence: A combined deep learning model

Abstract: To forecast the tourism demand across a set of tourist attractions with spatial dependence, a new model is proposed, which has three stages: tourist attraction selection, base predictor generation, and base predictor combination. In stage 1, a method for selecting associated attractions based on multi-dimensional scaling is used to determine the strength of the spatial dependence between each pair of attractions. In stage 2, a hybrid base predictor based on LSTM networks and Autoregressive model is developed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…However, existing studies have focused primarily on specific attractions [ 49 ], lacking an analysis of the distributional tendencies of touristic site within regions. Meanwhile, the traditional statistical survey data used in related research are limited in quantity and lack timeliness, while the emerging POI data, characterized by strong timeliness and large volume, are underutilized.…”
Section: Discussionmentioning
confidence: 99%
“…However, existing studies have focused primarily on specific attractions [ 49 ], lacking an analysis of the distributional tendencies of touristic site within regions. Meanwhile, the traditional statistical survey data used in related research are limited in quantity and lack timeliness, while the emerging POI data, characterized by strong timeliness and large volume, are underutilized.…”
Section: Discussionmentioning
confidence: 99%
“…AI-based methods have drawn considerable attention due to their ability of nonlinear modeling (Qiu et al ., 2021). Examples include bootstrap aggregation (Athanasopoulos et al ., 2017), time series bagging (Liu et al ., 2023), NNs (Cang, 2014; Claveria et al ., 2015a, b, 2017; Hu et al ., 2019; Hu, 2021), deep learning (Bi et al ., 2021, 2023; Han et al ., 2023; Law et al ., 2019; Xue et al ., 2023) and the support vector regression (SVR) (Chen, 2011). Wang et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…AI-based methods have drawn considerable attention due to their ability of nonlinear modeling (Qiu et al, 2021). Examples include bootstrap aggregation (Athanasopoulos et al, 2017), time series bagging (Liu et al, 2023), NNs (Cang, 2014;Claveria et al, 2015aClaveria et al, , b, 2017Hu et al, 2019;Hu, 2021), deep learning (Bi et al, 2021(Bi et al, , 2023Han et al, 2023;Law et al, 2019;Xue et al, 2023) and the support vector regression (SVR) (Chen, 2011). Wang et al (2023) proposed a multi-objective optimization algorithm for interval forecasting, Claveri and Torra (2014) showed that the ARIMA outperformed NNs over short horizons, and Volchek et al (2019) showed that NNs were more accurate than the seasonal autoregressive moving average with explanatory variables.…”
Section: Literature Review 21 Tourism Forecastingmentioning
confidence: 99%
“…The current TIS study mainly focuses on time series data, revealing that different tourism-based factors have short, medium, or long timescale effects [34,35]. For example, the weather proved to be a short-term impact on tourist volume [36,37]; extreme events proved to be a medium-term impact [8]; and scenic spots had a long-term impact [38]. In the post-COVID-19 era, examining the role of search data in travel has also become an important topic [39].…”
Section: Tourism Information Search (Tis)mentioning
confidence: 99%